Escavações arqueológicas na Igreja de S. Mamede (Torre de Moncorvo) - Lima, Alexandra Cerveira; Rodrigues, Miguel; Rebanda, Nelson; Gomes, Paulo Dórdio; Teixeira, Ricardo (Trabalhos de Antropologia e Etnologia, 2020)
.